Spicy sweet and sour sauce based on products from amazonian fruit farming and meliponiculture: technological development, physicochemical characterization, and sensory analysis (Revista Brasileira Multidisciplinar, 2025)
The Amazon region is a treasure trove of exotic ingredients with authentic flavors rich in bioactive substances that contribute to the socioeconomic development of traditional populations. The objective of this work is to analyze the acceptability and physicochemical characteristics of different formulations of a food sauce based on products from Amazonian fruit farming and meliponiculture. The sauce was made using samburá and stingless bee honey, cupuaçu pulp, pepper in varying proportions. The proximate composition ranged from 1.48 ± 0.06 g/100 g to 1.61 ± 0.12 g/100 g for proteins, 0.78 ± 0.14 g/100 g to 0.80 ± 0.05 g/100 g for lipids, and 68.74 ± 0.01 g/100 g to 66.95 ± 0.29 g/100 g for carbohydrates, determined according to official AOAC methods (Associaton of Official Analytical Chemists). The highest purchase intent percentages for the spicy sweet and sour sauce were observed for the formulation containing the lowest concentration of samburá and the highest concentrations of honey and cupuaçu pulp (Formulation A). It was possible to develop an innovative product with ingredients from Amazonian biodiversity, with good sensory acceptance and purchase intent. Additionally, the sauce showed desirable physicochemical properties and significant nutritional value, making it a viable alternative to family production systems, promoting the local bioeconomy.
Keywords: Natural products; Honey; Stingless bee; Cupuaçu